2016
DOI: 10.1105/tpc.15.00986
|View full text |Cite
|
Sign up to set email alerts
|

Feedback Regulation of DYT1 by Interactions with Downstream bHLH Factors Promotes DYT1 Nuclear Localization and Anther Development

Abstract: Transcriptional regulation is one of the most important mechanisms controlling development and cellular functions in plants and animals. The Arabidopsis thaliana bHLH transcription factor (TF) DYSFUNCTIONL TAPETUM1 (DYT1) is required for normal male fertility and anther development and activates the expression of the bHLH010/bHLH089/bHLH091 genes. Here, we showed that DYT1 is localized to both the cytoplasm and nucleus at anther stage 5 but specifically to the nucleus at anther stage 6 and onward. The bHLH010/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
99
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 90 publications
(100 citation statements)
references
References 46 publications
1
99
0
Order By: Relevance
“…The basic helix-loop-helix (bHLH) transcriptional factor DYSFUNCTIONAL TAPETUM1 (DYT1) is among the earliest acting male-specific regulators and is required for the normal development of tapetum by regulating the normal expression of more than 1,000 anther genes, and dyt1 mutants form abnormal prematurely vacuolated tapetal cells and lack mature pollen (Zhang et al, 2006;Feng et al, 2012;Gu et al, 2014;Zhu et al, 2015). In addition, bHLH010, bHLH089, and bHLH091 together are required for normal tapetum development and transcriptome and pollen fertility, forming both feed-forward and feedback loops with DYT1 (Zhu et al, 2015;Cui et al, 2016). Another bHLH transcription factor, ABORTED MICROSPORES (AMS), is a key regulator of anther transcriptome, sporopollenin biosynthesis and secretion, and pollen wall formation (Sorensen et al, 2003;Xu et al, 2010;Feng et al, 2012;Ma et al, 2012;Xu et al, 2014).…”
mentioning
confidence: 99%
“…The basic helix-loop-helix (bHLH) transcriptional factor DYSFUNCTIONAL TAPETUM1 (DYT1) is among the earliest acting male-specific regulators and is required for the normal development of tapetum by regulating the normal expression of more than 1,000 anther genes, and dyt1 mutants form abnormal prematurely vacuolated tapetal cells and lack mature pollen (Zhang et al, 2006;Feng et al, 2012;Gu et al, 2014;Zhu et al, 2015). In addition, bHLH010, bHLH089, and bHLH091 together are required for normal tapetum development and transcriptome and pollen fertility, forming both feed-forward and feedback loops with DYT1 (Zhu et al, 2015;Cui et al, 2016). Another bHLH transcription factor, ABORTED MICROSPORES (AMS), is a key regulator of anther transcriptome, sporopollenin biosynthesis and secretion, and pollen wall formation (Sorensen et al, 2003;Xu et al, 2010;Feng et al, 2012;Ma et al, 2012;Xu et al, 2014).…”
mentioning
confidence: 99%
“…However, there are substantial functional and structural differences (see below) between the C-terminal BIF/ACT-like domain of plant bHLH proteins (Feller et al, 2006;Kong et al, 2012;Cui et al, 2016) and the original ACT domain and previously reported ACT-like domain in other proteins (Chipman and Shaanan, 2001;Siltberg-Liberles and Martinez, 2009;Lang et al, 2014).…”
mentioning
confidence: 96%
“…DYT1 expression and function are precisely regulated by a set of interactions: On one hand, protein products of DYT1 downstream genes bHLH010/089/091 interact and form a feedforward loop with DYT1 to control the proper expression of shared downstream anther genes (Zhu et al, 2015); on the other hand, bHLH010/bHLH089/bHLH091 facilitates the stage-dependent nuclear-specific localization of DYT1 in a positive feedback regulatory loop enhancing DYT1 function (Cui et al, 2016).…”
mentioning
confidence: 99%
See 2 more Smart Citations